USER PARTICIPATION ON SYSTEM DEVELOPMENT, USER COMPETENCE AND TOP MANAGEMENT COMMITMENT AND THEIR EFFECT ON THE SUCCESS OF THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM (EMPIRICAL STUDY IN ISLAMIC BANK IN BANDUNG). Issue 2 (2015) - Nurhayati, Nunung; Mulyani, Sri
No abstract available